Pregnancy outcomes in liver and cardiothoracic transplant recipients: a UK national cohort study - Mohamed-Ahmed, O; Nelson-Piercy, C; Bramham, K; Gao, H; Kurinczuk, JJ; Brocklehurst, P; Knight, M (Public Library of Science, 2014)
Introduction There are an increasing number of reports of pregnancy in transplant recipients but many questions remain regarding the effect of the transplant on pregnancy outcome, the pregnancy on the graft and the medication on the fetus. The majority of studies reporting outcomes in transplant recipients have focused on women with kidney transplants, and have included retrospective, voluntary registries or single centre studies.